NURSING CARE ANALYSIS OF ARTIFICIAL RESPIRATORY MANAGEMENT IN STROKE-ASSOCIATED PNEUMONIA (SAP) PATIENTS: A CASE STUDY FROM ICU RSPAL DR. RAMELAN SURABAYA - Ababiel, Dinda Rimyatul (Universitas Nahdlatul Ulama Surabaya, 2024)
Introduction: Stroke-associated pneumonia (SAP) is a common complication of stroke, leading to ineffective airway clearance and potentially severe outcomes such as respiratory failure and death. Objective: This case study analyzes the nursing care provided to a SAP patient in the ICU of RSPAL Dr. Ramelan Surabaya, focusing on the application of artificial respiratory management to improve airway clearance Methods: Over five days, the nursing team implemented interventions, including Endotracheal Tube (ETT) care, which partially resolved the ineffective airway clearance. Results: This improvement was evident in the enhanced respiratory parameters and reduced secretion accumulation. Conclusions: The findings highlight the importance of diligent airway management in preventing respiratory complications in SAP patients.